A systematic review of the health effects of lead exposure from electronic waste in children - Belay Desye; Amensisa Hailu Tesfaye; Gete Berihun; Ayechew Ademas; Birhanu Sewunet (Frontiers Media S.A., 2023)
IntroductionElectronic waste (e-waste) is an emerging human and environmental problem. Lead (Pb) is one of the most dangerous chemicals for human health, and it is the most prevalent heavy metal pollutant in e-waste. Despite the rapid growth of e-waste globally and the health effects of Pb, there is little information regarding the effects of Pb exposure from e-waste on children. Therefore, the aim of this review was to provide concise information on the health effects of Pb exposure from e-waste on children.MethodsA comprehensive search of databases was undertaken using PubMed/MEDLINE, Cochrane Library, Science Direct, HINARI, African Journal Online (AJOL), and additional sources were searched up to November 25, 2022. Eligibility criteria were determined using Population, Exposure, Comparator, and Outcome (PECO). The guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) were used during the article selection process. The protocol of this systematic review was registered in the International Prospective Register of Systematic Reviews (Registration ID: CRD42022377028). The Joanna Briggs Institute (JBI) quality appraisal checklist was used to assess the quality of the included studies.ResultsFrom a total of 1,150 identified studies, 20 full-text studies were included in the systematic review. All most included studies were conducted in China recycling area for e-waste. The included studies were conducted with an exposed group versus a reference group. The majority of the included studies found that blood Pb levels were ≥5 μg/dl and that Pb exposures from e-waste were affecting children's health, such as a decrease in serum cortisol levels, inhibition of hemoglobin synthesis, impact on neurobehavioral development, affect physical development, etc.ConclusionLead exposure had a significant impact on children's health as a result of informal e-waste recycling. Therefore, formalizing the informal sector and raising public health awareness are important steps toward reducing Pb exposure from e-waste. Moreover, the concerned stakeholders, like national and international organizations, should work together to effectively manage e-waste.